Computational Analysis of Solvent Effects in NMR Spectroscopy - Dračínský, Martin; Bouř, Petr (Journal of chemical theory and computation, 2010)
Solvent modeling became a standard part of first principles computations of molecular properties. However, a universal solvent approach is particularly difficult for the nuclear magnetic resonance (NMR) shielding and spin-spin coupling constants that in part result from collective delocalized properties of the solute and the environment. In this work, bulk and specific solvent effects are discussed on experimental and theoretical model systems comprising solvated alanine zwitterion and chloroform molecules. Density functional theory computations performed on larger clusters indicate that standard dielectric continuum solvent models may not be sufficiently accurate. In some cases, more reasonable NMR parameters were obtained by approximation of the solvent with partial atomic charges. Combined cluster/continuum models yielded the most reasonable values of the spectroscopic parameters, provided that they are dynamically averaged. The roles of solvent polarizability, solvent shell structure, and bulk permeability were investigated. NMR shielding values caused by the macroscopic solvent magnetizability exhibited the slowest convergence with respect to the cluster size. For practical computations, however, inclusion of the first solvation sphere provided satisfactory corrections of the vacuum values. The simulations of chloroform chemical shifts and CH J-coupling constants were found to be very sensitive to the molecular dynamics model used to generate the cluster geometries. The results show that computationally efficient solvent modeling is possible and can reveal fine details of molecular structure, solvation, and dynamics.